A Chiral Metal-Organic 1D-Coordination Polymer Upon Complexation of Phenylene-Bridged Bipyrrole and Palladium (II) Ion - Nishinaka, Kumiko; Han, Jiandong; Han, Dongli; Liu, Yue; Du, Yanqing; Wang, Meiling; Eerdun, Chaolu; Naruse, Nobuyasu; Mera, Yutaka; Furusho, Yoshio; Tsuda, Akihiko (Frontiers in Chemistry, 2020)
Metal-organic 1D-coordination polymers, having unique electronic and optical properties, are expected to be a novel advanced functional material capable of fabricating smart plastics, films, and fibers. In this study, we have synthesized a novel metal-organic 1D-coordination polymer composed of a phenylene-bridged bipyrrole bearing N-alkylimino groups (BPI) and palladium(II) ion. The BPI and Pd(II) form square planar bis(bidentate) complex to form a metal coordinated pi-conjugation polymer (Poly-BPI/Pd). It is stable in solutions at room temperature, and allowed measurement of its average molecular weight in HPLC (Mw = 106000 and Mn = 18000, Mw/Mn = 5.88). It also provided a reversible multi redox profile in cyclic voltammetry, most likely originating form strong pi-electronic interactions between the BPI components via Pd ion. A variety of substituent groups can be attached to the imino-nitrogens of BPI. A coordination polymer composed of a BPI derivative bearing chiral alkyl chains and Pd(II) showed strong circular dichroism (CD) in the solution due to the unidirectional chiral conformation of the BPI components in the polymer backbone.